2020
DOI: 10.21203/rs.3.rs-48950/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and correlates of multiple non-communicable diseases risk factors among adults in Sudan: Results of the first national STEPS survey in 2016

Abstract: Background Non-communicable diseases (NCDs) are on the rise in low- and middle-income countries. The aim of this study was to assess the prevalence and correlates of multiple NCD risk factors among adults in Sudan. Methods Cross-sectional nationally representative data were analysed from 7,722 18–69 year-old individuals (median age = 36 years) that took part in the “2016 Sudan STEPS survey.” Results The prevalence of individual NCD risk factors was 94.6% inadequate fruit and vegetable intake, followed by hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The nationwide STEPS (STEPwise approach for Surveillance) survey of non-communicable disease risk factors carried out in 2019 showed a high prevalence of less than five servings of fruit and/or vegetable (96.7%), tobacco use (28.9%), overweight/obese (24.3%), raised blood pressure (24.5%), posing a greater threat for non-communicable diseases epidemic in future [ 7 ]. Several studies conducted have concluded that NCDs risk factors vary by socio-demographic characteristics [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nationwide STEPS (STEPwise approach for Surveillance) survey of non-communicable disease risk factors carried out in 2019 showed a high prevalence of less than five servings of fruit and/or vegetable (96.7%), tobacco use (28.9%), overweight/obese (24.3%), raised blood pressure (24.5%), posing a greater threat for non-communicable diseases epidemic in future [ 7 ]. Several studies conducted have concluded that NCDs risk factors vary by socio-demographic characteristics [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%